Application of PETCT imaging information combined with tumor markers in etiological screening of infectious and non-infectious ascites. Issue 12 (December 2020) - Gan, Xilun; Yang, Jianbo; Wang, Li; Tan, Beibei; Wang, Lisha
Abstract: In order to study the application value of PETCT image information combined with tumor markers in etiological screening of infectious and non-infectious ascites, ascites patients with unexplained etiological factors from the The Affiliated Hospital, Southwest Medical University were selected as the research objects, who were submitted to PET/CT scans and CT morphological scans for the semi-quantitative analysis of ascitic focus; in addition, the research objects were also submitted to chemiluminescence for the detection of concentrations of tumor markers in ascitic fluid, including carcinoembryonic antigen (CEA), alpha fetal protein (AFP), cancer antigen 125 (CA125), and carbohydrate antigen 19-9 (CA19-9). The results have shown that among the tumor markers CEA, AFP, CA125, and CA19-9, the tumor markers CEA, AFP, and CA19-9 had diagnostic reliability; in addition, compared with pure PET/CT imaging and ascites tumor marker detection, the combination of PET/CT imaging and tumor marker detection has more diagnostic value in infectious and non-infectious ascites etiology screening. Despite the deficiencies in the research process, it has provided a certain basis and ideas for subsequent research.